Factors in the development of university students’ job skills in business´ careers in Ecuador - Guim Bustos, Paola; Marreno Ancizar, Yaimary; Bustamante Ubilla, Miguel Alejandro (Revista de Ciencias Sociales, 2024)
Companies demand personnel who have the key´s competencies for business. This research aims to determine the development’s factors of job skills of university students of business’ careers in the province of Guayas, Ecuador. The design is quantitative, non-experimental and cross-sectional, a questionnaire with closed questions and a sample of 318 students was used. An exploratory factor analysis was developed through which key dimensions were configured. The results show five factors that intervene in the development of job competencies called competency learning, professional development planning, relationships and teamwork, professional development events, and work practice in companies. It is concluded that the first three factors identified explain between 17.9%, 11.8% and 10.2% of the variance, accumulating 40.02% of the total variance, this provides a clear orientation of which are the factors with the greatest impact on the development of labor skills. This work has theoretical implications, contributes to the literature with evidence of the factors that intervene in the development of job skills in business´ students, and has practical implications because university managers can focus on these factors to develop job skills in students.